Analytical Network Process Model-Based Halal Tourism Development Strategy in Banjarmasin City - Wahab, Abdul; Al Hadi, M Qoshid; Mahdiya, Ilma (EQUILIBRIUM, 2023)
This research seeks to determine the halal tourism development strategy in Banjarmasin City, prioritizing halal tourism development aspects, including tourist attraction, human resources, accessibility, regulations, marketing, and the environment. This research makes use of the Analytic Network Process approach. In-depth interviews and questionnaires were conducted with 12 expert informants consisting of academics, regulators, and practitioners. The results show that the priority issues are human resources, tourism services, regulations, and socialization. The priority solution to the four problems of developing halal tourism in Banjarmasin City is a regulatory solution. The strategies include 1) Improving the high-quality of human sources in halal tourism control; 2) Developing tourist services that are more Muslim-friendly; 3) Providing complete commitment and help from both the authorities and private zones in growing halal tourism; and 4) Accentuating the socialization and schooling concerning halal tourism to the network and tourism enterprise actors.